The Effects of Two Influential Early Childhood Interventions on Health and Healthy Behaviour. (7th December 2016) - Conti, Gabriella; Heckman, James J.; Pinto, Rodrigo
Abstract : This article examines the long‐term impacts on health and healthy behaviour of two of the oldest and most widely cited US early childhood interventions evaluated by the method of randomisation with long‐term follow‐up: the Perry Preschool Project (PPP) and the Carolina Abecedarian Project (ABC). There are pronounced gender effects strongly favouring boys, although there are also effects for girls. Dynamic mediation analyses show a significant role played by improved childhood traits, above and beyond the effects of experimentally enhanced adult socioeconomic status. These results show the potential of early life interventions for promoting health.